Fast corroding, thin magnesium coating displays antibacterial effects and low cytotoxicity. Issue 4 (21st April 2017) - Zaatreh, Sarah; Haffner, David; Strauß, Madlen; Wegner, Katharina; Warkentin, Mareike; Lurtz, Claudia; Zamponi, Christiane; Mittelmeier, Wolfram; Kreikemeyer, Bernd; Willumeit-Römer, Regine; Quandt, Eckhard; Bader, Rainer
Abstract: Bacterial colonisation and biofilm formation are characteristics of implant-associated infections. In search of candidates for improved prosthetic materials, fast corroding Mg-based coatings on titanium surfaces were examined for their cytotoxic and antimicrobial properties. Human osteoblasts and Staphylococcus epidermidis were each cultured on cylindrical Ti samples coated with a thin layer of Mg/Mg45 Zn5 Ca, applied via magnetron sputtering. Uncoated titanium samples served as controls. S. epidermidis was quantified by counting colony forming units. The biofilm-bound fraction was isolated via ultrasonic treatment, and the planktonic fraction via centrifugation. Biofilm-bound S. epidermidis was significantly decreased by approximately four to five orders of magnitude in both Mg- and Mg45 Zn5 Ca-coated samples after seven days compared to the control. The osteoblast viability was within the tolerance threshold of 70% stated in DIN EN ISO 10993-5:2009-10 for Mg (~80%) but not for Mg45 Zn5 Ca (~25%). Accordingly, Mg-coated titanium was identified as a promising candidate for an implant material with antibacterial properties and low cytotoxicity levels. The approach of exploiting fast corrosion contrasts with existing methods, which have generally focused on reducing corrosion.